Rural finance and poverty alleviation - Zeller, Manfred; Sharma, Manohar (International Food Policy Research Institute, 1998)
This report presents information on the credit constraints that poor rural households face ... in nine countries of Asia and Africa ( Bangladesh, Cameroon, China, Egypt, Ghana, Madagascar, Malawi, Nepal, and Pakistan). It uses this information to make the case for appropriate public intervention in strengthening rural financial markets and draws conclusions about areas where public resources may best be spent--Preface.